Small Business Simplification under Digitalization and Globalization Challenges: Teal Organizations Development (Economics and region, 2019)
In this article, the most possible simplicity of hierarchy and structure of organization are investigated on the principles of “teal” company. An innovative model of organization is build based on outsourcing, digitization, globalization and the idea of social utility.
Keywords: «teal» organization; self-management; hierarchy; management; business; digitization; outsourcing; globalization